Pengaruh Profitabilitas, Kepemilikan Manajerial, Leverage Dan Ukuran Perusahaan Terhadap Determinan Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2019-2021 - Namira Ufrida Rahmi; Richard Denrisc; Nora Nora; Shania Shania; Irna Triannur Lubis (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The research intent to find out to what extent the profitability impact, managerial ownership,leverage, also company size about the determinants of dividend policy in manufacturing companies on the Indonesia Stock Exchange for the 2019-2021 period. In this study, the population are 56 manufacturing companies. Samples were taken through purposive sampling technique so that 22 companies were obtained in a 3 year period, so a total of 66 samples were obtained. The data was taken from www.idx.co.id (website) which is secondary data. The results showed that profitability formulated with ROE had no partial effect on the determinants of dividen policy, managerial ownership had a partial effect on the determinants of dividend policy, leverage was used to measure DER on the determinants of dividend policy which had a partial effect, LN was used to measure firm size which had a partial effect on the determinants of dividend policy. Then simultaneously ROE,DER, Managerial Ownership, and LN affect the determinants of dividend policy. Keywords : Profitability, Managerial Ownership, Leverage, Firm Size, and Dividen Policy